Advances in Cholangiocarcinoma Treatment in the Personalized Medicine Era - Kathrin Dvir; Gliceida M Galarza Fortuna; Nathaly Cortez; Veronica Guerra; Mike Cusnir (Open Journal of Hepatology - Peertechz Publications, 2020)
Cholangiocarcinoma is amongst the most common primary tumors of the liver, second only to hepatocellular carcinoma, and it accounts for approximately 15% of primary hepatic malignancies [1]. Cholangiocarcinoma is sub-classified as intrahepatic (ICCA), perihilar (PCCA) or distal (DCCA), according to its anatomical location [2]. Regardless of location, cholangiocarcinoma carries a poor prognosis, mainly due to paucity of effective therapy options and advanced disease at presentation. The American Cancer Society determined a 5-year relative survival rate of 8% for all patients with intrahepatic bile duct cancer and 10% for its extrahepatic counterpart. Even localized disease carries poor survival of 24% and 15% for ICCA and extrahepatic cholangiocarcinoma, respectively [3].